2017
DOI: 10.1177/1479972317707652
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and infection control of airway clearance devices used by CF patients

Abstract: Respiratory treatment for cystic fibrosis (CF) patients includes use of respiratory devices. Contamination of airway clearance devices has not been adequately explored. We aimed to determine whether airway clearance devices are contaminated after use and whether cleaning guidelines for nebulizers are as effective for airway clearance devices. Patients brought their airway clearance devices to the clinic. Swabs from the devices were taken before and after cleaning and were cultured for bacterial counts. Total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Potential CF pathogens have been found on nebulizers [29][30][31][32][33] but only in a few instances have these been consistent with pathogens identified from the patient's respiratory samples [34,35]. Increased use of aerosolized medications was found to be a risk factor for PA acquisition in a mathematical model of PA risk factors [36].…”
Section: Acquisition From the Healthcare Environmentmentioning
confidence: 99%
“…Potential CF pathogens have been found on nebulizers [29][30][31][32][33] but only in a few instances have these been consistent with pathogens identified from the patient's respiratory samples [34,35]. Increased use of aerosolized medications was found to be a risk factor for PA acquisition in a mathematical model of PA risk factors [36].…”
Section: Acquisition From the Healthcare Environmentmentioning
confidence: 99%
“…For more information, the reader is referred to a recent publication on infection prevention and control guidelines for the growing number of respiratory devices. 132…”
Section: Infection Controlmentioning
confidence: 99%
“…There is a lack of scientific evidence available pertaining to the optimum temperature of water specifically for washing nebulisers; however, nebuliser manufacturers generally recommend warm or hot water in their instructions ( table S2 ). A study looking at the cleaning of airway clearance devices showed complete or partial eradication of bacterial yield in 50% and 30%, respectively, of contaminated airway clearance devices when they were soaked for 10 min in hot water (temperature unspecified) and detergent, and rinsed with hot water before air drying [ 13 ].…”
Section: Evidence-based Guidancementioning
confidence: 99%
“…In theory, air drying the nebuliser should significantly reduce the risk of nosocomial infection. In the study by M anor et al [ 13 ], simple cleaning and air drying without disinfection was found to be effective in most cases. Air drying has been advocated as a method of drying to cause least recontamination of cleaned parts [ 62 ] and is now the drying technique of choice advocated by many nebuliser manufacturers.…”
Section: Dryingmentioning
confidence: 99%